Awareness on Non-Communicable Diseases among Service Recipients in a Municipal Health Center of Dang District, Nepal - Pokhrel, Arun Kumar (Haimaprabha, 2026)
Non-communicable diseases (NCDs) such as hypertension, diabetes, and obesity are emerging as major public health challenges in Nepal. Rapid urbanization, lifestyle changes, and limited awareness have accelerated their prevalence, particularly in semi-urban communities. These conditions often remain undiagnosed until complications arise, underscoring the importance of early detection and preventive strategies. A descriptive cross-sectional screening study was conducted at Tulsipur Municipal Health Center, Ward-5 Buspark, Dang District, Nepal. A total of 226 individuals (149 female, 77 male) voluntarily participated. Standardized diagnostic tools including weighing scales, blood pressure apparatus, glucometers, and urine test strips were used to assess overweight, hypertension, elevated blood sugar, and proteinuria. Data were analyzed using descriptive analysis .The screening revealed a considerable burden of NCD risk factors. Of the participants, 44.7% were overweight, 25.7% had elevated blood sugar, 14.6% were hypertension, and 12.8% showed proteinuria. Female participants consistently demonstrated higher absolute numbers across most indicators, while the proportion of hypertension was slightly higher among males. These findings highlight the silent progression of chronic conditions within the community and the urgent need for early intervention. This study demonstrates that NCD risk factors are widespread in semi-urban Nepal, reflecting both national and global trends. The high prevalence of overweight, hyperglycemia, hypertension, and proteinuria emphasizes the necessity of routine screening, awareness campaigns, and gender-sensitive interventions. Despite limitations such as convenient sampling and absence of detailed behavioral data, the study provides valuable insights into community health status. Strengthening primary healthcare services, promoting healthy lifestyles, and integrating NCD prevention into routine care are critical steps to reduce the growing burden of chronic diseases in Nepal.